The Effect Of Green Marketing, Brand Image, And Green Perceived Risk On Aqua Consumer Purchase Decisions With Trust As An Intervening Variable On The BPA Issue In Reusable Gallon Packaging - Nabilah; Sutrisno (LPPM STMIK Mardira Indonesia, 2026)
This study examines the impact of Green Marketing, Brand Image, and Green Perceived Risk on the Purchase Decisions of AQUA consumers, with Consumer Trust serving as an intervening variable regarding the BPA concern in reusable gallon containers. This research employed a quantitative approach, disseminating online surveys via Google Forms to 300 participants who had used AQUA products and were aware of the BPA concern. The sample strategy employed was purposive sampling, and the data analysis techniques were validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and Sobel testing. The findings indicated that Green Marketing, Brand Image, and Green Perceived Risk exerted a favorable and significant influence on Purchase Decisions and Consumer Trust. Furthermore, Consumer Trust exerted a favorable, significant impact on Purchase Decisions and effectively mediated the effects of Green Marketing, Brand Image, and Green Perceived Risk on Purchase Decisions among AQUA consumers. This study demonstrates that consumer trust is a crucial factor in sustaining purchasing decisions amid escalating concerns about BPA in reusable gallon packaging.